Pengembangan Media Audio Visual Berbantuan Canva pada Tema 7 Subtema 2 Kelas IV SDN 060857 Tembung T.A 2022/2023 - Efi Rasmasari br Sinaga; Laurensia Masri Perangin-angin; Demmu Karo-Karo; Risma Sihotang; Lala Jelita Ananda (Journal on Education, 2024)
This research was carried out starting from the problems experienced in learning in class IV SDN 060857 Tembung, especially in the use of media in the learning process which was less creative and varied, resulting in students having difficulty understanding learning material and during learning students were less active. This study aims to produce to test the feasibility, practicality, and effectiveness of audio-visual media based on Canva. This study uses the ADDIE model which consists of analysis, design, development, implementation, and evaluation. Learning media developed through validation from questionnaire validators, material validators, media validators, and educational practitioners. The results of the feasibility study of audio-visual media based on Canva show that the media is "Very Eligible" with details of obtaining an average percentage of the questionnaire with a percentage of 94% which is in the "very feasible" category. Material validation obtained a score of 53 with a percentage of 88% which was in the "very feasible" category. Media validation obtained a score of 37 with a percentage of 82% which was in the "very feasible" category. The practicality of media by class IV teachers at SDN 060857 Tembung is 97% which is in the "very practical" category. The effectiveness of the media was obtained from the post-test of 81% in the "very effective" category.